Measurement of Unsupported Applications used in Indonesia Popular Websites - Nugroho, Pascal Alfadian; Steven, Hizkia (Universitas Ahmad Dahlan, 2021)
A security vulnerability exists in unsupported systems, and using applications supported by their maintainer help to reduce attacks based on such vulnerabilities. However, website administrators may ignore this exercise due to various reasons. This research measures the top 1,500 websites in Indonesia on how much of them are using supported applications to prevent such attacks, based on the application version number. The measurement is performed automatically using the Wappalyzer tool. From such measurement, we found that most of the applications detected do not contain version information (70%) or invalid version number (11%). We also found that more than half of the websites measured contain at least one unsupported application. In terms of the applications used, we found that many Nginx users worryingly do not keep their server version updated, while Apache and WordPress did a good job in keeping their users using the most recent version. This study highlights the need for website administrators to have their applications up to date to the supported versions, as well as for application developers to promote application updates to their users.